2014
DOI: 10.1002/lary.25085
|View full text |Cite
|
Sign up to set email alerts
|

Sleep magnetic resonance imaging with electroencephalogram in obstructive sleep apnea syndrome

Abstract: 2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
(44 reference statements)
0
23
2
1
Order By: Relevance
“…Previous sleep MRI studies have demonstrated retropalatal and retroglossal airway collapse in subjects with OSA [6]. In this study, we found that retropalatal airway collapse is common in all OSA subjects, which is [6][7][8][9]15]. We did not, however, find any isolated retroglossal airway collapse in subjects with severe OSA as described in previous imaging studies [7,9].…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Previous sleep MRI studies have demonstrated retropalatal and retroglossal airway collapse in subjects with OSA [6]. In this study, we found that retropalatal airway collapse is common in all OSA subjects, which is [6][7][8][9]15]. We did not, however, find any isolated retroglossal airway collapse in subjects with severe OSA as described in previous imaging studies [7,9].…”
Section: Discussioncontrasting
confidence: 51%
“…In this study, we found that retropalatal airway collapse is common in all OSA subjects, which is [6][7][8][9]15]. We did not, however, find any isolated retroglossal airway collapse in subjects with severe OSA as described in previous imaging studies [7,9]. All of our severe OSA subjects showed retroglossal or retropalatal airway collapse in combination with lateral pharyngeal wall collapse.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Electroencephalograms are recorded synchronously with MRI to objectively determine sleep and wakefulness [79]. Respiration, heart rate, and oxygen saturation signals are simultaneously recorded to infer central or obstructive apneic events [49].…”
Section: Synchronized Acquisitionmentioning
confidence: 99%